Sustainable Marketing Strategy in The Remanufacturing Industry: A Soft Systems Methodology Approach - Anik Nur Habyba; Delfitriani; Triwulandari Satitidjati Dewayana; Debbie Kemala Sari; Emelia Sari; Indah Permata Sari (Business Review and Case Studies, 2024)
Background: PT. X is one of Indonesia's heavy equipment component companies with a remanufacturing division that aims to achieve sustainability goals by implementing sustainable marketing. Even though the manufacturing industry has enormous potential, implementing sustainable marketing in this sector still faces many challenges.Purpose: This study aims to analyze the critical challenges and propose a conceptual model for sustainable marketing implementation in the remanufacturing industry.Design/methodology/approach: The SSM framework analyzes complex systems, emphasizing human and organizational factors, to guide the application of sustainable marketing in remanufacturing. Before developing the conceptual model, a sustainable marketing mix analysis was conducted to identify challenges that hinder successful implementation.Findings/results: Several important variables were identified to increase the successful implementation of sustainable marketing for remanufactured products. Prices, product quality, and green public awareness need to be improved. The complex implementation of the sustainable marketing mix at PT X can be seen through the rich picture system. Apart from that, based on the root definition, it can show that many stakeholders are involved in supporting the success of this system, and it must also be supported by government policy. Several essential activities are identified in the conceptual model, such as the role of the remanufacturing division in PT X.Conclusion: This research shows that the success of implementing sustainable marketing on remanufactured products is highly dependent on increasing prices, product quality, and public awareness, as well as involving various stakeholders and support from government policies.Originality/value (State of the art): This research contributes to a holistic approach that combines systems analysis with sustainable marketing elements and focuses on the remanufacturing industry.Keywords: sustainable marketing, remanufacturing industry, marketing mix, soft system methodology, conceptual model